Mewujudkan Nilai-Nilai Pancasila Melalui Kegiatan Sosial Di Perguruan Tinggi - Sulthaanah Maharani; M. Sultan Habibullah (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research aims to explore the implementation of Pancasila values through social activities in higher education using a qualitative approach. The literature study will explore the theoretical basis related to Pancasila values, value education, and social activities in the context of higher education. This understanding will strengthen in-depth analysis related to the concept and integration of Pancasila values. This research aims to identify supporting and inhibiting factors in realizing Pancasila values through social activities. The results of the analysis are expected to provide a deep understanding of the contribution of higher education in the character building of students and society.